PWE-035 Patients' Experience Of Colonoscopy In The English Bowel Cancer Screening Programme. (9th June 2014) - Ghanouni, A; Plumb, A; Rees, CJ; Hewitson, P; Miller, H; Bevan, R; Von Wagner, C
Abstract : Introduction: In the English Bowel Cancer Screening Programme, colonoscopy is the standard investigation to exclude cancer in participants who receive a positive faecal occult blood test result. A questionnaire is sent to all patients 30 days post-test. These data were used to assess patients' experience of colonoscopy. Methods: Anonymised data were extracted from the Bowel Cancer Screening System. These included all patients who had colonoscopy between 01/01/11 and 31/12/12. Questionnaire items on the pre-test experience (whether patients understood the risks/benefits), the hospital experience (the test itself, issues of dignity/privacy) and post-test complications (bleeding/pain) were analysed. Pearson chi-square tests were used to compare experiences by gender, high vs. low levels of socioeconomic deprivation (using Index of Multiple Deprivation scores), and whether patients reported receiving sedation or not. Results: After excluding patients outside the target date range and those who did not have colonoscopy, 76, 717 patients were eligible for analysis, of whom 60, 581 (79.0%) responded to the questionnaire. Nearly all patients felt they understood the risks (95.7%) and benefits (98.2%) of the test, and 97.8% felt the preparation instructions were clear. Comparison by gender and deprivation did not yield clinically meaningful (≥3%) differences. In terms of the hospital experience, virtually all patients felt they were treated with respect (98.5%) and had privacy (98.0%), but 20.8% experienced more discomfort than expected (although only 5.2% asked for the test to be stopped/paused). Procedural discomfort was moderated by gender, with more women than men reporting higher-than-expected discomfort (25.4% vs. 17.9%; p < 0.0005), and requesting that the test be stopped/paused (7.1% vs. 3.9%; p < 0.0005). Use of sedation showed only a weak association with patient experience: 22.2% of sedated vs. 20.2% of non-sedated patients reported unexpected discomfort; 6.4% vs. 4.8% asked for the test to be stopped/paused; both p-values <0.0005). Post-test, 14.3% of patients reported pain and 6.9% reported rectal bleeding. Pain was more common in women (18.0% vs. 11.9%; p < 0.0005) but there were no other clinically meaningful differences post-test related to gender or deprivation level. Conclusion: Most patients referred for colonoscopy as part of the Bowel Cancer Screening Programme have a positive colonoscopy experience. The most negative aspect of the experience was the test being unexpectedly uncomfortable. Patients are extensively counselled pre-procedure but more emphasis on managing expectations, along with continued measures to reduce discomfort and pain are required, particularly for women. Disclosure of Interest: None Declared.